2013
DOI: 10.1093/eurpub/ckt035
|View full text |Cite
|
Sign up to set email alerts
|

Urban greenways have the potential to increase physical activity levels cost-effectively

Abstract: The Greenway intervention could be cost-effective at improving physical activity levels. Although the direct health gains are predicted to be small for any individual, summed over an entire population, they are substantial. In addition, the Greenway is likely to have much wider benefits beyond health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 30 publications
0
66
0
Order By: Relevance
“…Two studies looked at interventions in a number of European cities (49,53). Nine studies were undertaken in England (35, 38, 41, 55-57, 60, 61, 63), one in Scotland (59), one in Ireland (40) and one in Northern Ireland (65). Six studies were undertaken in the United States (37, 44-46, 58, 62), one in New Zealand (48) and seven studies were undertaken in Australia (34,42,50,54,64,66,67).…”
Section: Setting and Location (Cheers Item 5)mentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies looked at interventions in a number of European cities (49,53). Nine studies were undertaken in England (35, 38, 41, 55-57, 60, 61, 63), one in Scotland (59), one in Ireland (40) and one in Northern Ireland (65). Six studies were undertaken in the United States (37, 44-46, 58, 62), one in New Zealand (48) and seven studies were undertaken in Australia (34,42,50,54,64,66,67).…”
Section: Setting and Location (Cheers Item 5)mentioning
confidence: 99%
“…Only eight studies reported their perspectives explicitly. Four applied a health sector perspective (58,62,64,65), one a public payer perspective (26), two a societal perspective (66,67) and one used both a health sector and a societal perspective (35). Economic evaluation entails the incremental assessment of both the costs and benefits of an intervention against an alternative option.…”
Section: Study Perspective and Comparators (Cheers Items 6-7)mentioning
confidence: 99%
See 3 more Smart Citations